The doctrine of God ; part 1 - Barth, Karl, 1886-1968.; Torrance, Thomas Forsyth, 1913-; Bromiley, Geoffrey William (Edinburgh, Scotland : T. and T. Clark, 1957)
Includes indexes.
Original German ed. : Die Kirchliche Dogmatik, II : Die Lehre von Gott, 1
Keywords: God